5 CM : SEMIOTICS PERSPECTIVE ON HILL JOURNEY - Muhammad Fadli; Salsa Solli Nafsika (Universitas Pendidikan Indonesia, 2021)
This article aims to discuss signs or semiotic analysis in the climbing journey carried out in the 5CM film, using Charles Sander Peirce's semiotic analysis. In this film tells the story of the struggle of climbing Mount Semeru which was carried out by 5 friends and one of the younger brothers of one of them, in the ascent there was a lot of cohesiveness and solidity between them, the climbing struggle was not easy to pass but they were able to achieve their goals thanks to hard work and mutual support. complement each other. From this phenomenon, the writer analyzes the images presented using the semiotic theory of Charles Sanders Pierce. This analysis will be based on a classification based on objects with the main subject of study on icons, indexes and symbols according to the subject of Charles Sanders Pierce's Semiotics study. The method used in the preparation of this article is a qualitative analysis method by observing and analyzing the material carefully by the author. This film clearly describes the climbing journey of 5 friends who went through many obstacles and threats to reach the top as their goal. Things about the world of climbing in general are also depicted in this film which is considered to provide education to the audience. In the pictures that are presented, many meanings are conveyed and that is what will be the object of study in this article. Hopefully this article can provide some information and can be a reference in the next writing.